Novel foldamer structural architecture from cofacial aromatic building blocks - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, Pattuparampil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2009)
This communication demonstrates the utility of peri-substituted 1,8-diphenylnaphthalene as an effective building block for the construction of novel conformationally ordered synthetic oligomers displaying cofacial structural features.